(3GdWGbI aj eUQ h JMOjGJ GdeSJbHds - (3CMeO, SjO YGThQs ((3CSjhW (B[(3eUQ(B]s [(3O(B. (3f(B]s, 2010)
(3jYfi gPG GdcJGH HeUGOQ GdWGbI GdeJLOOI h GdHOjdI, HGdJQcjR Ydi eUQ h YQV ebJVH dJdc GdeUGOQ YQHjG(B. (3h jSJgd GdYQV HGdWGbI GdfaWjI h CHYGOgG, Ke JYQja HCge eUGOQ GdWGbI GdeJLOOI (B: (3GdWGbI GdTeSjI, WGbI GdQjGM, WGbI CehGL GdHMGQ h GdeMjWGJ, WGbI GdeO h GdLRQ, WGbI GdeSGbW GdeGFjI, WGbI Lha GdCQV, GdWGbI GdgLjfI, GdWGbI GdgjOQhLjfjI, NdGjG GdhbhO h OhQgG, WGbI GdcJdI GdMjhjI HeG JJVefg ef CSGdjH eYGUQI ef EfJGL GdEjKGfhd GdMjhj h GdOjRd GdMjhj h GdZGR GdMjhj, Edi LGfH GdZGR GdWHjYj h GdeSGd cWGbI HOjdI(B. (3jdj Pdc YQV dhVY GdWGbI GdeJLOOI h GdHOjdI YQHjG, Ke hVY eUGOQ Jdc GdWGbI aj eUQ JaUjdG HGdJQcjR Ydi (B: (3GdWGbI GdTeSjI, WGbI GdQjGM, GdWGbI GdeGFjI, WGbI GdcJdI GdMjhjI ceUGOQ eJLOOI ddWGbI, h GdZGR GdWHjYj cWGbI HOjdI(B. (3ceG jJfGhd GdYQV JaUjdG GdWGbI GdfhhjI aj eUQ, h eNJUQG aj GdOhd GdYQHjI GdJj CHOJ GgJeGeG HgPG GdeUOQ ddWGbI(B. (3h jNJJe GdYQV HNdGUI YGeI h JhUjGJ h ebJQMGJ ddfghV HGdGSJaGOI ef eUGOQ GdWGbI GdeJLOOI h GdHOjdI aj eUQs
11 21
Keywords: (3GdWGbI GdTeSjIs; (3GdWGbI GdeJLOOI h GdHOjdIs; (3GdWGbI GdfaWjIs; (3GdWGbI GdfhhjIs; (3GdWGbIs